2017
DOI: 10.1590/2179-8087.001916
|View full text |Cite
|
Sign up to set email alerts
|

Saturação por Bases no Crescimento e na Nutrição de Mudas de Ipê-Amarelo

Abstract: RESUMOO ipê-amarelo (Tabebuia serratifolia) é uma espécie florestal com potencial madeireiro, porém, pouco utilizada em plantios florestais, devido à escassez de informações sobre sua produção tanto em viveiro quanto no campo. Diante disso, realizou-se experimento com o objetivo de verificar os efeitos da calagem no crescimento e na nutrição de mudas de T. serratifolia. O calcário foi misturado ao solo Latossolo Vermelho distrófico de textura franco-arenosa, em sacolas plásticas com capacidade para 2,5 kg. Os … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Base saturation is an important indicator of soil fertility since high levels of V% suggest high concentration of cations, such as Ca² + , Mg² + and K + , and decreased levels of H + and exchangeable Al 3 + (GORSKI et al, 2019), denoting a suitable environment for plant growth. Similarly to the present study, Vieira and Weber (2017) found that base saturation at 70% allowed for better development of Tabebuia serratifolia seedlings in comparison to lower levels. Conversely, for Toona ciliata var.…”
Section: Resultssupporting
confidence: 89%
“…Base saturation is an important indicator of soil fertility since high levels of V% suggest high concentration of cations, such as Ca² + , Mg² + and K + , and decreased levels of H + and exchangeable Al 3 + (GORSKI et al, 2019), denoting a suitable environment for plant growth. Similarly to the present study, Vieira and Weber (2017) found that base saturation at 70% allowed for better development of Tabebuia serratifolia seedlings in comparison to lower levels. Conversely, for Toona ciliata var.…”
Section: Resultssupporting
confidence: 89%
“…The lack of response to liming by the species may have resulted from its ability to adapt to soils such as those found in the Cerrado biome, which presents high acidity level and low nutrient availability. The chemical limitations of the soil mean that the phytophysiognomy of this biome is featured by the presence of tolerant species, although these species face limited growth and development due to nutrient deficiency (Vieira & Weber, 2017). The aforementioned authors assessed the effects of liming on the growth and nutrition of Tabebuia serratifolia seedlings in an experiment using soil with 26.5% base saturation and found better growth in 70% BS.…”
Section: Resultsmentioning
confidence: 99%
“…Despite its importance, H. serratifolius is rarely utilized in forest plantations due to the lack of information regarding its development in both nursery and field conditions [16], being propagated mainly by seeds but also demonstrating germination and preservation issues, such as reduced physiological potential during storage [17,18,19].…”
Section: Introductionmentioning
confidence: 99%